Gamerville - Christmas, Johnnie (New York, NY : Harper Alley, an imprint of HarperCollinsPublishers, 2024)
"Max Lightning is howling at the moon--he's finally qualified for Gamerville, a championship where players compete to be top dog in the multiplayer video game Lone Wolf of Calamity Bay. But his dreams of domination are doomed when his parents send him to Camp Reset. Gone are the long nights of downing energy drinks and getting copious amounts of screen time. They've been replaced with fresh air and group activities under the hot sun--a shock to the system for a lone wolf like Max. Can Max escape Camp Reset and level up at Gamerville, or has he finally played his last match?"--
Keywords: Video gamers -- Comic books, strips, etc; Video games -- Comic books, strips, etc; Technology -- Comic books, strips, etc. -- Social aspects; African American boys -- Comic books, strips, etc; Camps -- Comic books, strips, etc; Outdoor recreation -- Comic books, strips, etc; Friendship in children -- Comic books, strips, etc; Video gamers -- Fiction; Video games -- Fiction; Technology -- Fiction; African American boys -- Fiction; Camps -- Fiction; Outdoor recreation -- Fiction; Friendship -- Fiction; Cartoons and comics; Graphic novels; Graphic novels